Developing notetaking skills in a second language : insights from classroom research - Siegel, Joseph, 1979- (Abingdon : Routledge, 2021)
Developing Notetaking Skills in a Second Language combines theoretical perspectives with an analysis of empirical classroom studies and offers a detailed discussion that increases pedagogical awareness of factors impacting second language (L2) notetaking performance and instruction. Based on original research and including descriptions of classroom practices and samples of student work, the book provides insights on a range of topics relevant to L2 notetaking. The book emphasizes the challenges that many students from different international backgrounds face when taking notes in an L2 and outlines a five-stage pedagogic cycle for notetaking that can be applied to any listening text. It also explores the dialogic potential of notes for stimulating class discussion about notetaking strategies. This book will be of great interest for teachers, academics, scholars, and postgraduate students in the fields of applied linguistics, L2 and foreign language education. It will also be a useful resource for those in charge of teacher education and postgraduate TESOL, L1, and L2 listening researchers and psycholinguists.
OCLC-licensed vendor bibliographic record.
Keywords: Second language acquisition; Note-taking.; EDUCATION / General